Si3N4-BN-SiCN ceramics with unique hetero-interfaces for enhancing microwave absorption properties. Issue 9 (1st May 2021) - Xue, Jimei; Ren, Fangyuan; Dong, Yongpeng; Wei, Hanjun; Yang, Fan; Cheng, Laifei
Abstract: SiCN-based ceramics with broadband and strong microwave absorption properties are desired for the structural and functional integration of ceramic matrix composites. The elemental composition and thermal expansion coefficients of the ceramics matrix crucially affect its microstructure and electromagnetic wave (EMW) absorption properties. BN layer with lower electrical conductivity and higher specific area, exhibits both the impedance matching characteristic and EMW attenuation in the process of multiple reflections, electrical conductivity loss, dipole polarization and interfacial polarization. Therefore, Si3 N4 -BN-SiCN ceramics, which were synthesized using chemical vapor infiltration (CVI) method, construct unique hetero-interface of Si3 N4 -BN, Si3 N4 –SiCN and BN-SiCN. Therefore, the Si3 N4 -BN-SiCN ceramics have outstanding EMW absorption performance and realize an effective absorption bandwidth (EAB) that covers the whole X band and the minimum reflection coefficient (RC) reaches -18.43 dB at a thickness of 3.37 mm.